Operative Dictations in Ophthalmology - Rosenberg, Eric D.; Nattis, Alanna S.; Nattis, Richard J. (Springer International Publishing : Imprint: Springer, 2017)
This book provides residents with a comprehensive review of surgical cases within the field of ophthalmology. Operative Dictations in Ophthalmology touches on important steps within each surgical case, indications for the procedure, possible complications, and a sample dictation. The review serves as both a preparation and debriefing for each surgeon, or surgeon in training, by improving comprehension time, cultivating surgical forethought, and refining post operative dictations. .
Keywords: Medicine.; Ophthalmology.; elektronické knihy; electronic books